2008
DOI: 10.1002/jor.20831
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐corrosion of stainless steel by osteoclasts—in vitro evidence

Abstract: Most metals in contact with biological systems undergo corrosion by an electrochemical process. This study investigated whether human osteoclasts (OC) are able to grow on stainless steel (SS) and directly corrode the metal alloy leading to the formation of corresponding metal ions, which may cause inflammatory reactions and activate the immune system. Scanning electron microscopy analysis demonstrated long-term viable OC cultures and evident resorption features on the surface of SS discs on which OC were cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 40 publications
7
59
0
2
Order By: Relevance
“…Moreover, corrosion and leaching of metal ions from metallic counterfaces into body fluids are also significant problems during long term use. For example, stainless steel has been extensively used in many biomedical applications, but the products of its corrosion and released Cr, Ni, Mn, and Mo ions [2,3], can trigger several adverse reactions, from simple allergies and hypersensitivity to the metals to tumour formation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, corrosion and leaching of metal ions from metallic counterfaces into body fluids are also significant problems during long term use. For example, stainless steel has been extensively used in many biomedical applications, but the products of its corrosion and released Cr, Ni, Mn, and Mo ions [2,3], can trigger several adverse reactions, from simple allergies and hypersensitivity to the metals to tumour formation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of metals, particularly when it occurs in the mouth, is of the electrolytic type due to the interaction of two alloys causing galvanic corrosion 15 . One of the fundamental conditions for using metal materials in the oral environment is that they resist the corrosive action of saliva, alkaline and acid foods [16][17] as well as pH and temperature variations. One of the materials used in Orthodontics, which is more susceptible to corrosion, is silver soldering 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence is evidenced by findings of elevated levels of a range of immune cells and markers found in peri-implant tissue at various time intervals after implantation, including CD3 + and CD4 + T lymphocytes, CD11c + macrophages/dendritic cells, and cells with abundant expression of MHC class II (human leukocyte antigen-DR) (dendritic cells) [158][159][160]. In addition, significant levels of metal ions can be found in various parts of the body, including capsular and periprosthetic tissues, distant organs (liver, spleen, lymph nodes), and in the urine and serum of patients undergoing total hip arthroscopy [161][162][163][164][165][166].…”
Section: Pathophysiology Of Metal Hypersensitivity Reactionsmentioning
confidence: 99%
“…Cadosch et al [161] demonstrated that osteoclast precursors can grow and differentiate on stainless steel, aluminum, and chromium in vitro and can directly corrode the metal surface and release metal ions.…”
Section: Pathophysiology Of Metal Hypersensitivity Reactionsmentioning
confidence: 99%